"Homo reciprocusSeneka, Paulus en weldoenerskap 1 - Joubert, Stephan (Hervormde teologiese studies, 1999)
"Homo reciprocus": Seneca, Paul and benefaction Reciprocity was basic to most forms of social interaction in the ancient Mediterranean world. Any exchange of services/gits was based on the principle that the obligations incurred between two parties required an adequate response. In his ethical treatise on beneit exchange, "De beneficiis,"Seneca presents an idealistic reinterpretation of the basic tenets of benefaction by providing a "lex vitae", a law of conduct, according to which the giving of beneits becomes an intrinsically rewarding experience in itself. On his part, the apostle Paul conceptualises his "ecumenical" collecion for the Jerusalem church in terms of the principles inherent to beneit exchange in the Graeco-Roman world. He involves his communities as beneiciaries in the reciprocal relationship between himself and Jerusalem. In Romans 15:25-31, when the acceptance of the collecion hangs in the balance, Paul reinterprets the reciprocal relationship with Jerusalem in terms of altruistic Christian principles. From this new angle of incidence his churches are presented as having successfully completed the collection since they unselishly fulilled their moral duies towards the latter.